2005
DOI: 10.1007/s00431-005-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical data and factors associated with poor outcome in pneumococcal meningitis

Abstract: We carried out a 4-year study of 159 children (ages 1 month-14 years) with pneumococcal meningitis. The study was divided into two periods: the retrospective period (1998-2000: 107 patients), and the prospective period (2001-2002: 52 patients). About 2/3 of the children were under 2 years of age: 72 (45%) were under 1 year of age and 38 (24%) had meningitis during the second year of life. One-third of the patients had signs of otitis media; convulsions were more frequent in patients under 1 year compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…Hence this paper should provide useful results for economic evaluation of present and future vaccines against pneumococcal infection. n/a n/a n/a n/a Auburtin 29 40.0% 25.0% 5.0% n/a n/a 10.0% n/a n/a Auburtin 32 34.3% 13.3% n/a n/a n/a 8.6% n/a n/a Bedford 3 49.7% n/a n/a n/a n/a n/a n/a n/a Benca 33 23.3% n/a n/a n/a n/a n/a n/a n/a Buckingham 34 n/a n/a n/a n/a n/a 6.7% n/a n/a Casado-Flores 35 36.3% 45.2% n/a 11.8% n/a 21.5% n/a n/a Davis 36 33.7% 21.2% n/a n/a 3.8% 17.3% n/a n/a De Lalla 37 4.5% n/a n/a n/a n/a n/a n/a n/a Eriksson 38 n/a 6.5% n/a n/a n/a n/a n/a n/a Faella 39 21.4% 7.1% n/a n/a n/a n/a n/a n/a Fiore 40 13.8% n/a n/a n/a n/a n/a n/a n/a Fortnum 41 n/a 4.5% n/a n/a n/a n/a n/a n/a Grimwood 42 47.1% n/a n/a n/a n/a n/a n/a n/a Hanna 43 n/a 3.0% n/a n/a n/a 3.0% n/a n/a Hoogman 44 n/a n/a n/a n/a n/a n/a n/a 27.8% Husain 45 n/a 18.9% n/a n/a 11.3% 7.5% n/a 7.5% Ishidawa 30 35.7% n/a n/a n/a n/a n/a n/a n/a Ispahani 4 26.2% 13.7% n/a n/a n/a 9.8% n/a n/a Kaaresen 46 42.9% 28.6% n/a n/a n/a n/a n/a n/a Kallio 47 37.5% 37.5% n/a n/a n/a n/a n/a n/a Kastenbauer 48 n/a 25.8% n/a n/a n/a n/a n/a n/a Kellner 17 41.4% 17.2% n/a n/a n/a n/a n/a n/a Kennedy (control) 49 32.6% n/a n/a n/a n/a n/a n/a n/a Kennedy (intervention) 49 11.4% n/a n/a n/a n/a n/a n/a n/a Kilpi 27 50.0% 50.0% n/a n/a n/a n/a n/a n/a King (control) 50 16.7% 16.7% n/a n/a n/a n/a n/a n/a King (intervention) 50 42.9% 28.6% n/a n/a n/a n/a n/a n/a King 51 28.2% n/a n/a n/a n/a 11.2% n/a 6.7% Kirkpatrick 52 20.0% 13.4% n/a n/a n/a 1.5% n/a n/a Kornelisse 53 36.2% 18.8% 2.9% n/a 10.1% 10.1% n/a 7.2% Korshin 54 42.9% n/a n/a n/a n/a n/a n/a n/a Kragsbjerg 55 29.2% 4.2% n/a n/a 4.2% n/a n/a n/a Lazzarini 56 25.0% n/a n/a n/a n/a n/a n/a n/a ...…”
Section: Discussionmentioning
confidence: 98%
“…Hence this paper should provide useful results for economic evaluation of present and future vaccines against pneumococcal infection. n/a n/a n/a n/a Auburtin 29 40.0% 25.0% 5.0% n/a n/a 10.0% n/a n/a Auburtin 32 34.3% 13.3% n/a n/a n/a 8.6% n/a n/a Bedford 3 49.7% n/a n/a n/a n/a n/a n/a n/a Benca 33 23.3% n/a n/a n/a n/a n/a n/a n/a Buckingham 34 n/a n/a n/a n/a n/a 6.7% n/a n/a Casado-Flores 35 36.3% 45.2% n/a 11.8% n/a 21.5% n/a n/a Davis 36 33.7% 21.2% n/a n/a 3.8% 17.3% n/a n/a De Lalla 37 4.5% n/a n/a n/a n/a n/a n/a n/a Eriksson 38 n/a 6.5% n/a n/a n/a n/a n/a n/a Faella 39 21.4% 7.1% n/a n/a n/a n/a n/a n/a Fiore 40 13.8% n/a n/a n/a n/a n/a n/a n/a Fortnum 41 n/a 4.5% n/a n/a n/a n/a n/a n/a Grimwood 42 47.1% n/a n/a n/a n/a n/a n/a n/a Hanna 43 n/a 3.0% n/a n/a n/a 3.0% n/a n/a Hoogman 44 n/a n/a n/a n/a n/a n/a n/a 27.8% Husain 45 n/a 18.9% n/a n/a 11.3% 7.5% n/a 7.5% Ishidawa 30 35.7% n/a n/a n/a n/a n/a n/a n/a Ispahani 4 26.2% 13.7% n/a n/a n/a 9.8% n/a n/a Kaaresen 46 42.9% 28.6% n/a n/a n/a n/a n/a n/a Kallio 47 37.5% 37.5% n/a n/a n/a n/a n/a n/a Kastenbauer 48 n/a 25.8% n/a n/a n/a n/a n/a n/a Kellner 17 41.4% 17.2% n/a n/a n/a n/a n/a n/a Kennedy (control) 49 32.6% n/a n/a n/a n/a n/a n/a n/a Kennedy (intervention) 49 11.4% n/a n/a n/a n/a n/a n/a n/a Kilpi 27 50.0% 50.0% n/a n/a n/a n/a n/a n/a King (control) 50 16.7% 16.7% n/a n/a n/a n/a n/a n/a King (intervention) 50 42.9% 28.6% n/a n/a n/a n/a n/a n/a King 51 28.2% n/a n/a n/a n/a 11.2% n/a 6.7% Kirkpatrick 52 20.0% 13.4% n/a n/a n/a 1.5% n/a n/a Kornelisse 53 36.2% 18.8% 2.9% n/a 10.1% 10.1% n/a 7.2% Korshin 54 42.9% n/a n/a n/a n/a n/a n/a n/a Kragsbjerg 55 29.2% 4.2% n/a n/a 4.2% n/a n/a n/a Lazzarini 56 25.0% n/a n/a n/a n/a n/a n/a n/a ...…”
Section: Discussionmentioning
confidence: 98%
“…The classical triad of fever, nuchal rigidity, and altered mental status is found for 60% of patients (336). S. pneumoniae meningitis is a severe disease, which is reflected by the high rate of patients presenting with focal neurological abnormalities (40%) and seizures (25%) (11,57,242,340,355). One of five patients is admitted to the hospital in a comatose state (340).…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%
“…For children, a review of outcomes showed an overall mortality rate of 15% (19). Recent case series of childhood pneumococcal meningitis reported rates of 8% (11,57). A study including children with pneumococcal meningitis in a resource-poor setting reported a mortality rate of 37% (248).…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%
See 1 more Smart Citation
“…Whilst clinically effective, cost-effectiveness has been debated due to high price, the lack of quality long-term outcome data and whether short-term herd immunity is important [1,5,6,18,19]. Data on the outcome of pneumococcal meningitis (PM) come from uncontrolled patient series [7,8,15,22], studies that do not distinguish between PM and other forms of meningitis [2] or adult studies [24,36]. The paucity of quality outcome data may, in part, explain the previous delay in adopting this vaccine for routine use [14].…”
mentioning
confidence: 99%